(untitled) (Ukrainian Journal of Ophthalmology, 2025)
We reviewed studies on the role of neopterin as a biomarker of various infectious and non-infectious diseases and presented the benefits of measuring the levels of this biomarker in biological fluids in disorders involving cell-mediated immunity. The results of relevant studies in multiple fields of medicine are described herein. Measuring neoptherin levels in biological fluids may be beneficial not only for diagnosis or verification of a particular disease, but also for differentiation of the disease from others resembling it, assessment of treatment efficacy and prediction of subsequent disease course.